Effects of Inhaled Salbutamol Versus 0.9% Normal Saline on Duration of Hospital Stay in Transiennt Tachypnea of Newborn - Anam, Ayesha; Javeed, Asif; Shahid, Sidra; Manzoor, Saima (Biological and Clinical Sciences Research Journal, 2025)
Transient tachypnea of the newborn (TTN) is a common cause of respiratory distress in neonates, often requiring prolonged hospitalization and oxygen therapy. Enhancing lung fluid absorption using beta-agonists like salbutamol may reduce disease duration and hospital stay. Objective: To compare the effects of inhaled salbutamol versus 0.9% normal saline on the duration of hospital stay and oxygen therapy in neonates diagnosed with TTN. Methods: This randomized controlled trial was conducted at the department of Pediatric Medicine in the Ibn-e-Siena Hospital Multan from November 2023 to November 2024 and included 60 term or late preterm neonates with clinical and radiographic evidence of TTN. Participants were randomly assigned to receive either a single dose of inhaled salbutamol (0.15 ml/kg in 4 ml saline) or 4 ml of 0.9% saline via nebulization. Respiratory parameters were monitored, and the primary outcome was duration of hospital stay. Secondary outcomes included duration of oxygen therapy and improvements in respiratory rate and oxygen saturation. Data were analyzed using SPSS version 23.0, and an independent t-test was applied. A p-value ≤ 0.05 was considered statistically significant. Results: The mean duration of oxygen therapy was significantly lower in the salbutamol group (7.13 ± 2.16 hours) compared to the control group (11.67 ± 5.97 hours; p < 0.001). The mean duration of hospital stay was also shorter in the salbutamol group (3.33 ± 1.16 days) than in the control group (4.90 ± 1.49 days), although the difference was not statistically significant (p = 0.229). Baseline characteristics such as gestational age, birth weight, and maternal age were comparable between the groups. Conclusion: Inhaled salbutamol is effective in reducing the duration of oxygen therapy in neonates with TTN. Although not statistically significant, it may also contribute to shorter hospital stays. This intervention may be particularly beneficial in resource-constrained settings. Further larger-scale studies are warranted.